2017
DOI: 10.2147/ccide.s119040
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of conventional and semilunar coronally positioned flap techniques for root coverage in teeth with cervical abrasion restored with pink resin

Abstract: Gingival recession is the most common mucogingival defect, characterized by apical migration of the gingival margin from the cementoenamel junction and root exposure. Several surgical techniques are reported for the treatment of gingival recession. Here we present a comparison of the conventional (coronally advanced flap) and semilunar coronally positioned flap techniques for root coverage in teeth with cervical abrasion restored with pink resin that mimics the color of the gingiva. Although the conventional t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 17 publications
0
4
0
2
Order By: Relevance
“…Santos et al . in 2017[ 9 ] conducted a study to compare the clinical outcomes of the semilunar coronally repositioned flap (SLCRF) and coronally advanced flap (CAF) procedure in the treatment of maxillary Miller's Class I GR defects. The results of the study concluded that both the procedures provided stable clinical outcome in terms of recession coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Santos et al . in 2017[ 9 ] conducted a study to compare the clinical outcomes of the semilunar coronally repositioned flap (SLCRF) and coronally advanced flap (CAF) procedure in the treatment of maxillary Miller's Class I GR defects. The results of the study concluded that both the procedures provided stable clinical outcome in terms of recession coverage.…”
Section: Discussionmentioning
confidence: 99%
“…Ugyanakkor az NCCL-val társuló ínyrecessziók kezelésében több randomizált klinikai vizsgálat értékelte sikeresnek a szubgingivális GIC biokompatibilitását MCAF, illetve MCAF+SCTG műtétek után. A kombinált restauratív sebészi technikák között találunk az irodalomban MCAF [20,36,48,66,69], MCAF+SCTG [3,67,21], MCAF+kollagén xenograft [49] kombinált műtéteket. Egy tanulmány SCTG és GIC kom binált kezelés után hónapokkal az üvegionomer tömés felszínén klinikailag mérhető kúszó tapadásról számolt be [3].…”
Section: Megbeszélésunclassified
“…A korábban idézett esettanulmányok mellett [3,65,49,69,21,25,20] egy, a jelen vizsgálatunkhoz hasonló közleményt találtunk, ahol egyik oldalon CAF, a másik oldalon CAF+GIC műtétek után fél és két évvel értékelték eredményeiket. A féléves adatok szerint nem találtak szignifikáns különbséget a két oldal között, sem a fognyaki fedésben, recesszió-csökkenésben.…”
Section: Megbeszélésunclassified
“…As a result, for patients with good dental hygiene, surgical treatment of gingival recession was necessary to reduce these problems. Sub-epithelial connective tissue grafts (SCTG), coronally advanced flaps (CAF), semilunar coronally advanced flaps, laterally positioned flaps, and free gingival grafts have all been used to address gingival recessions [ 5 , 6 , 7 , 8 , 9 ]. The primary downside of the SCTG procedure is the need for donor tissue.…”
Section: Introductionmentioning
confidence: 99%